The Effects of Fe2O3 Nanoparticles on Physiology and Insecticide Activity in Non-Transgenic and Bt-Transgenic Cotton - Van Nhan, Le; Ma, Chuanxin; Rui, Yukui; Cao, Weidong; Deng, Yingqing; Liu, Liming; Xing, Baoshan (Frontiers in Plant Science, 2016)
As the demands for nanotechnology and nanoparticle (NP) applications in agriculture increase, the ecological risk has drawn more attention because of the unpredictable results of interactions between NPs and transgenic crops. In this study, we investigated the effects of various concentrations of Fe2O3 NPs on Bt-transgenic cotton in comparison with conventional cotton for 10 days. Each treatment was conducted in triplicate, and each experiment was repeated three times. Results demonstrated that Fe2O3 nanoparticles (NPs) inhibited the plant height and root length of Bt-transgenic cotton and promoted root hairs and biomass of non-transgenic cotton. Nutrients such as Na and K in Bt-transgenic cotton roots increased, while Zn contents decreased with Fe2O3 NPs. Most hormones in the roots of Bt-transgenic cotton increased at low Fe2O3 NP exposure (100 mg·L−1) but decreased at high concentrations of Fe2O3 NPs (1000 mg·L−1). Fe2O3 NPs increased the Bt-toxin in leaves and roots of Bt-transgenic cotton. Fe2O3 NPs were absorbed into roots, then transported to the shoots of both Bt-transgenic and non-transgenic cottons. The bioaccumulation of Fe2O3 NPs in plants might be a potential risk for agricultural crops and affect the environment and human health.